Correlation of various risk management factors for risk control at general hospital: A cross-sectional study - Retno Marlangen; Nani Sari Murni; Erma Gustina (Lentera Perawat, 2025)
Background: Hospitals are high-risk workplaces requiring effective risk management to protect healthcare workers, patients, and the environment. In Indonesia, implementing Hospital Occupational Health and Safety (K3RS) remains challenging, particularly in identifying factors that influence successful risk control. Objective: To determine the factors associated with risk management at Dr. Rivai Abdullah General Hospital in Banyuasin and to identify the most dominant factor. Methods: A quantitative study with a cross-sectional design involved 77 healthcare workers and managerial staff. Data were collected using a structured questionnaire and secondary documents, then analyzed with Spearman’s rho correlation and multiple logistic regression. Results: Significant factors associated with risk management included occupational health training (p=0.02), attitude (p=0.006), human resources availability (p=0.007), budget (p=0.010), facilities and infrastructure (p<0.001), effective communication (p<0.001), environment (p<0.001), and hospital occupational health and safety implementation (p=0.003). The most dominant factor was the environment (OR=0.016; 95%CI 0.002–0.130), explaining 35.1–48.1% of risk management variation. Conclusion: Risk management is influenced by both individual and organizational factors, with the environment as the key determinant. Hospitals should prioritize improving the work environment, strengthening K3RS programs through monitoring and evaluation, enhancing inter-unit communication, and ensuring adequate support in human resources, budget, and training.